The Role of Local Government and Environmental Management in Managing Tidal Floods in Bintan Regency - Aldy Wiguna; Rudy Subiyakto (Center for Maritime Policy and Governance Studies. Universitas Maritim Raja Ali Haji. Indonesia, 2024)
Indonesia is highly vulnerable to natural disasters, with tidal floods being a significant concern in Bintan Regency due to its exposure to sea tides and extreme weather events. The local government's role and environmental management strategies are crucial in mitigating these risks. This research seeks to evaluate these aspects by focusing on the measures implemented by Bintan Regency to manage tidal floods. The study employs a qualitative approach, relying on literature reviews to collect data from various sources such as scientific journals, books, research reports, and other relevant documents. This method provides a comprehensive understanding of the current practices and effectiveness of flood management and environmental management strategies in Bintan Regency. The research findings indicate that the Bintan Regency local government has undertaken significant initiatives to reduce tidal flood risks. These initiatives include spatial planning that integrates disaster risk considerations, the development of flood management infrastructure, and community education programs aimed at increasing preparedness. The effective implementation of environmental management practices, including the use of advanced technology for monitoring and evaluation, has been instrumental in these efforts. The local government’s approach reflects a proactive stance in addressing the challenges posed by tidal floods, emphasizing both preventative measures and responsive strategies. The study concludes that a holistic and sustainable approach is essential for effective tidal flood management. The integration of comprehensive spatial planning, infrastructure development, community engagement, and modern technology forms a robust framework for disaster mitigation.